Association of genetic polymorphisms in vascular endothelial growth factor with susceptibility to coronary artery disease: a meta-analysis - Wen-Qi Ma; Ying Wang; Xi-Qiong Han; Yi Zhu; Nai-Feng Liu (BMC, 2018)
Abstract Background Single nucleotide polymorphisms (SNPs) located in the vascular endothelial growth factor (VEGF) gene may be correlated with the susceptibility to coronary artery disease (CAD) - although results have been controversial. The aim of this meta-analysis is to clarify the effects of VEGF -2578A/C (rs699947), −1154G/A (rs1570360), +405C/G (rs2010963), and + 936C/T (rs3025039) polymorphisms on CAD risk. Methods Pooled odds ratio (OR) and corresponding 95% confidence intervals (CIs) were calculated to estimate the strength of the association between VEGF gene polymorphisms and CAD risk. Fixed- or random-effects model was used depending on the heterogeneity between studies. Results In total, 13 eligible articles containing 29 studies were analysed. The pooled analysis indicated that the VEGF gene polymorphisms of rs699947, rs2010963, and rs3025039 were associated with an increased risk of CAD, whereas no significant associations were observed with the rs1570360 polymorphism. A subgroup analysis stratified by ethnicity revealed that the rs699947 and rs3025039 polymorphisms were associated with CAD risk in Asian populations. In addition, stratification by control source indicated an increased risk of CAD susceptibility with the rs699947 polymorphism for population-based studies of reduced heterogeneity. Conclusions In summary, we concluded that the VEGF gene polymorphisms rs699947, rs2010963, and rs3025039 are correlated with an elevated CAD risk.